The Effect of Aerobic Endurance Training towards the Physical Condition of Deltra Volleyball Athletes Blok D Sitiung II - Imam Fitroh Munandar; Muhammad Sukron; Dian Estu Prasetyo (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This research was motivated by the low physical condition of Deltra Sitiung II volleyball athletes. Efforts to overcome these problems require aerobic endurance training. This study aims to determine whether aerobic endurance training has a significant effect on the physical condition of Deltra volleyball athletes. This research is an experimental research type, while the research design used is a